A auto-estima da criança que sofre violência física pela família - Bonavides, Syrleine Maria Penaforte Bastos (2005)
This research investigates the self-esteem of children who suffered physical violence by family members. Seven children took part in the research: three boys and four girls, aged between six and twelve years old. The analysis were done from the constructed data obtained from: semi-structured interview, activities about human feelings, activities that included facial expressions, unfinished phrases, Pinocchio s story, a drawing of a family and a drawing of their own family. Data were analyzed from the Content Analysis. The Thematic Units were: violence, intrafamily violence, and self-esteem. The synthesis of the categories studied evidenced that the physical violence and the psychological violence present in the lives of children affect the positive development of their self-concept and, consequently, of their self-esteem. Among the results, we emphasize some negative feelings that are present in children s lives such as fear, a sense of guilt, and sadness, arising out of the situations of violence they have experienced